Relevansi Pendidikan Spiritual dalam Tembang Lir Ilir Karya Sunan Kalijaga Dengan Masyarakat Madani. - Riyan Ali Mahmudi; Murdianto Murdianto; Tamrin Fathoni; Rohmat Arkham (Muaddib: Jurnal Pendidikan Agama Islam, 2023)
The development of globalization is increasingly eroding the social order. become a threat to a nation So it is necessary to have a revolutionary change in the social order that is dreamed of One that can be used as a reference is the song Lilir Ilir by Sunan Kalijaga where each line contains a very deep message related to the values needed to create good and dignified society. in this case about the Relevance of Spiritual Education in Sunan Kalijaga's Lir Ilir Song with Civil Society. This type of research was carried out in the form of a literature study with a qualitative approach which was then explained by means of descriptive analysis. The source of data in this study is the text of Tembang Lir Ilir by Sunan Kalijaga which has been validated from several relevant sources. Data collection techniques through documentation. Meanwhile, to analyze the data, namely the method of content analysis and general conclusions. In conclusion, Tembang lir ilir explains how efforts are made to form a civil society system, namely pious, spiritual, pious ritual, pious social and the principle of living together based on the core values of Islamic sharia teachings (Maqashid As-Syari'ah).